Dietetic assessment and intervention in lung cancer. Issue 4 (December 2019) - Phillips, Iain; Hug, Adele; Allan, Lindsey; Ezhil, Veni
Abstract : Purpose of review: Systemic therapy for lung cancer is increasing in intensity and duration. European nutrition guidelines suggest screening for weight loss and malnutrition, however acknowledges there is a lack of evidence. We discuss current data round this issue and identify opportunities for further research. Recent findings: International guidelines now exist to aid the definition of weight loss in cancer, including cachexia, sarcopenia and malnutrition. These allow consistent definition of overlapping, but distinct clinical syndromes. Nutritional status can be assessed in a range of ways including questionnaires, functional assessments, blood markers, physical activity, weight and BMI. Weight loss is commonly associated with a proinflammatory state. Future treatment is likely to be a combination of dietetic support and pharmacological treatment of cachexia. Summary: There is a paucity of data on dietetic intervention. It is potentially quick, inexpensive and patient specific, using a holistic approach to aid patients who are malnourished or at risk of malnutrition. Lung cancer-related weight loss is common, further strategies are needed to effectively assess and intervene. Dietetic intervention has the potential to improve patients' quality of life and outcomes.